ANALYSIS OF DISAGREGATE TRIP GENERATION AND TRIP ATTRACTIONS OF CRIPPLES IN YOLA NORTH LOCAL GOVERNMENT AREA, ADAMAWA STATE, NIGERIA - JONATHAN BALA, MALGWI; ISTIFANUS, SERAH; UMAR, HASHIM (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
The study analysed disaggregate trip generation and trip attraction of cripples in Yola North Local Government Area, Adamawa State, Nigeria. Multi-stage sampling techniques were used to select the respondents for the study. This sampling techniques allows smaller groups to be successively selected from large populations to form the sample population and makes data collection more practical for large populations, especially when a complete list of all elements of a population does not exist. A total of 254 well structure questionnaires were administered to the respondents with the help of a research assistant. The data collected were analysed using frequency, percentage and regression analysis. The study found that the common modes of transport are; bus, car, tricycle, motor cycle, bicycles, wheelchair and trekking. The spatial distribution of trips of the respondents shows some form of regularity in spatial dimension which are influence by the pattern of Land uses both residential and non-residential which serve as the basis for trip generation and trip attraction in Yola North Local Government Area. The regression analysis for trip generation shows that types of transport and reasons for mode choice accounts for about 76% of the sum total of the variation on the dependent variable. Similarly, trip attraction shows that the trip attraction of cripples was found to be explains by variables of household size, reasons for mode choice, distance of trips, educational levels and age of the cripples. These variables therefore, accounts for 0.98% of the total variation in trip attraction of cripples. Based on the findings of the Study, the study recommended that Public transport system should introduce transport fare concessory per trip for cripples. This will help in building a caring and inclusive transport system for cripples in the study area.